Pelaksanaan Pembelajaran Mata Kuliah Kewiraan Menurut Persepsi Mahasiswa - Suharjo Dwijosumarto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Implementation of Instruction in Kewiraan Course According to the Students. The purpose of this research was to know the effectiveness of teaching-learning process in Kewiraan based on the students' perception. The study involved 47 students of the Department of Elementary School Teacher Education, State University of Surabaya. The data were collected by questionnaire and analyzed statistically by percentage and mean measures. The result showed that the quality of the teaching learning process was good enough. The mean score was 7.639, whereas the other components of the teaching-learning process range between fair (16 %) to good (84 %).